Validation of Humanitarian Love Scale (HLS) through Exploratory and Confirmatory Factor Analysis - Abu Zahrin, Syaidatun Nazirah; Nazilah, A.; Radin Hasbani, Radin Anis Adlina; Yunos, Nasruddin; Siran, Fatin Hazwani; Mohamad Jodi, Khairul Hamimah; Aziz, Azwira Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Measuring love for humanity is an important step for developing a loving, caring and peaceful community. However, there is a gap between a valid and reliable instrument to measure the love of humanity in Malaysia. This study aims to validate the Humanitarian Love Scale (HLS) by using exploratory and confirmatory analysis with a sample of 500 volunteers. The HLS is a set of questionnaires that has 50 items with 10 domains. It were namely Altruism, Philanthropy, Caring, Tolerance, Shared Values, Love of Kindness, Moderation, Obeying Law, Empathy and Social Responsibility. Two steps of analysis have been done through Exploratory Analysis (EFA) and followed by Confirmatory Factor Analysis (CFA). The analysis was using SPSS and Amos version 22.0. The Cronbach's alpha coefficient for subscale ranging from 0.660 to 0.818 and overall scale 0.888. Finally, after the confirmatory process through CFA, there are only 29 items were chosen as an HLS Instrument, with 9 new domains, excluding Moderation. The study found that HLS was a reliable and valid scale to measure the love of humanity based on the domains measured. This study supports the conceptual framework and provides practical implication in the field of social psychology and psychological testing.